1991
DOI: 10.1002/jor.1100090113
|View full text |Cite
|
Sign up to set email alerts
|

Variables affecting disc size in the lumbar spine of rabbits: Anesthesia, paralysis, and disc injury

Abstract: Methods have been developed that permit repetitive radiographic measurement of the lumbar intervertebral disc space in a rostral-caudal direction (width) in the anesthetized laboratory rabbit. Using isolated control discs and injured discs in which narrowing has been induced for chronic and acute periods, the widths of the lumbar intervertebral disc spaces determined ratio-graphically correlate with widths determined histologically (p less than 0.000, r = 0.75). Both an increase (widening) and a decrease (narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, Oshima et al reported that the swelling pressure in bovine tail discs is similar to that in human lumbar discs, indicating that the prevailing compressive stress of the tail discs is probably of similar magnitude to lumbar discs. Anaesthesia [110,135] produces a similar increase in disc thickness as that which results from applying distraction forces of 60% bodyweight (c. 0.25 MPa) to the tail, which suggests that the ambient loading is of similar magnitude. 2.…”
Section: Mechanical Modelsmentioning
confidence: 80%
“…However, Oshima et al reported that the swelling pressure in bovine tail discs is similar to that in human lumbar discs, indicating that the prevailing compressive stress of the tail discs is probably of similar magnitude to lumbar discs. Anaesthesia [110,135] produces a similar increase in disc thickness as that which results from applying distraction forces of 60% bodyweight (c. 0.25 MPa) to the tail, which suggests that the ambient loading is of similar magnitude. 2.…”
Section: Mechanical Modelsmentioning
confidence: 80%
“…We have found limitation of mobility in the herniated segment [13], which could correspond to increased forces applied through the spinal muscles [11]. An association between annular fracture and discal protrusion has already been described [6,17], but this may not be correct because of possible histological artefacts [5].…”
Section: Discussionmentioning
confidence: 86%
“…Bipedal rats have been used to reproduce the human situation [15], the maintenance of forced bending of the spine has been studied [9,11] and cyclical changes have been applied to the disc [1,7,9]. Others have used direct action on the disc by damaging the annulus [8], increasing disc pressure by the injection of liquid [11], or resection of the posterior arch to produce instability [13]. Takenaka produced an acute disc hernia by bending the rat's tail [14], but this method is difficult to reproduce or quantify.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the swelling pressure of bovine tail discs is similar to that of human lumbar discs [80] and the loading in bovine discs is similar to that of human [81,82]. Besides, bovine tail discs are also less gel-like compared to immature porcine discs which resemble discs in developed human more closely.…”
Section: Use Of Bovine Cellsmentioning
confidence: 93%